Institusionalisasi Partai Aceh: Patronase dan Konsolidasi dalam Transisi Demokrasi Pasca Konflik - Darwin, Rizkika Lhena (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2016)
AbstractIn a democratic transition in post-conflict areas, the institutionalization of political party influence on the consolidation of the party so the impact on the realization of a political strategy. This paper wants to describe the patterns used in the process of institutionalization of the Aceh Party as a local political party in Aceh, where there is a transformation from insurgents to the political parties as well as the achievement of the consolidation of the party. This paper concludes that the party born from a guerrilla movement requires a pattern of patronage to save his authority on the realization of democratic politics in the post-conflict era. It is considered essential to achieve the consolidation of the party both in internal and external (read: constituent) party. Keywords: institutionalization, party politics, patronage, consolidation AbstrakDalam transisi demokrasi di daerah pasca konflik, pelembagaan partai politik sangat berpengaruh terhadap konsolidasi partai sehingga berdampak pada realisasi strategi politik. Tulisan ini ingin menggambarkan pola yang digunakan dalam proses institusionalisasi Partai Aceh sebagai partai politik lokal di Aceh, dimana terjadi transformasi dari gerilyawan ke partai politik serta pencapaian konsolidasi partai. Tulisan ini menyimpulkan bahwa partai yang lahir dari gerakan gerilya membutuhkan pola patronase untuk menyelamatkan otoritasnya pada realiasi politik di era demokrasi pasca konflik. Hal ini dianggap penting untuk mencapai konsolidasi partai baik di internal maupun eksternal (baca:konstituen) partai.Kata kunci: institusionalisasi, partai politik, patronase, konsolidasi